Emotional intelligence - (:unkn) unknown (My University, 2001)
Emotional intelligence is defined as having the personal skills that characterize a rich and balanced personality. Emotional intelligence includes non-cognitive skills and capabilities that determine the person's ability to cope with environmental demands and pressures. The concept of emotional intelligence has emerged as a result of the inability of the existing measures to predict the degree of success in life. The more emotional skills a person has, the less risk there is of developing psychiatric problems. The main elements of emotional intelligence include self-awareness, managing emotions, self-motivation, empathy, and handling relationships. Emotional activities can be considered as the result of interplay between the neural activity of the hypothalamus and the activity of higher brain centers. Amygdala is central to fear and related acute emotional reactions. The interactive work of the cortical and subcortical circuits, especially the connections between the amygdala and the prefrontal areas constitute the components that make up the emotional intelligence. Although some emotional traits seem to be genetically determined, emotional intelligence skills are to a great extent learned through experience. It is also possible to improve emotional intelligence skills through professional guidance. Emotional intelligence contributes to success in educational or organizational context, effective leadership, and physical health.
Keywords: Brain; Emotional intelligence; Health; Leadership; Success